Dietary Intake of pregnant women: A cross-sectional descriptive study - Salehi, Sayed Omid (2020)
Introduction: One of the most important stages of women's life which make several physiological and mental changes in women is pregnancy period. Based on the importance of nutrition in pregnancy period, having a healthy and suitable diet can ensure a secure pregnancy period and child birth; therefore, this study was done to determine the nutritional pattern of pregnant women who refer to health centers. Methods: The participants in this study were 235 pregnant women who referred to urban health centers and based on the age of pregnancy, they were passing the second trimester of pregnancy. The required information in this cross-sectional descriptive study were collected by the two sectional questionnaire which containing Food Frequency Questionnaire (FFQ) with 48 items and demographic characteristics questionnaire. The analysis of Food Frequency Questionnaire was done by NUT4 software and the analysis of data was done by SPSS software and statistic descriptive tests such as (affluence, average and standard deviation). To comparison the number of allowed using units of food groups of pregnant women in the second trimester of pregnancy with the average of the number of using units of food groups by population under study, the statistic T-test was used. Results and Discussion: The results of this study showed that 94.5% of pregnant women were using bread and cereals food group more than allowed range. The amount of using meat and protein food group, fruits group and fats group was in allowed range. The amount of using vegetables group and milk and dairy group was less than allowed range. About the amount of energy intake of food, the results of this study showed that 66.4% of participants in this study got more energy than allowed range. Conclusions: Pregnant women who participate in this study based on the intake of macronutrient and energy intake were in unappropriated situation, because of this, it is needed to give enough information about food groups and the needed amount of them in pregnancy period to all the pregnant women who refer to health centers.